Reserve Currency Blocs : A Changing International Monetary System? - Tovar Mora, Camilo (IMF Working Papers; Working Paper, 2018)
What is the extent of currency diversification in the international monetary system? How has it evolved over time? In this paper, we quantify the degree of currency diversification using regression methods of currency co-movements to determine the extent to which national currencies across the world belong to a reserve currency bloc. We then use these estimates to calculate the economic size of each currency bloc. A key contribution of our paper is that we quantify the size of the Chinese renminbi bloc. Our analysis suggests that the international monetary system has transitioned from a bi-polar system - consisting of the U.S. dollar and the euro - to a tri-polar one that includes the renminbi. The dollar bloc is estimated to continue to dominate, having the largest share in global GDP (40 percent), followed by the renminbi (30 percent) and the euro blocs (20 percent). The geographical area of influence for the RMB bloc appears to be most evident among the BRICS' currencies. The British pound and the Japanese yen blocs appear to play minor roles.